PERFORMANCE EVALUATION OF HEXACOPTER UAV (ANGRAU - PUSHPAK) SPRAYER FOR MANAGEMENT OF LATE LEAF SPOT IN GROUNDNUT CROP - A.SAMBAIAH*, L. PRASANTHI, B.SREE LAKSHMI, CH. MADHURI, K. PURNA CHANDRA RAO, N. VENKATA LAKSHMI; K. GURAVA REDDY (The Journal of Research ANGRAU, 2024)
This study was conducted to assess the efficacy of low volume UAV sprayer (25 L ha-1) for controlling late leaf spot, (Nothopassalora personata) disease of groundnut in Krishna agroclimatic zone of Andhra Pradesh. The experiment was conducted during late rabi season between 2021-2022 and 2022-23. To comprehend the suitability of UAV spraying in groundnut to control late leaf spot, restricted randomised block design (RRBD) was imposed in the field of five acres with five treatments viz., T1-100%, T2-75% and T3-50% RDP with UAV spraying and T4-100% RDP with human back power sprayer and T5-control plot with only water spraying with UAV. To control late leaf spot, CIB & RC recommended chemicals carbendazim 12% + mancozeb 63% WP at 61 DAS and followed by hexaconazole 5% EC at 68 DAS were sprayed as per the experimental treatment protocols. The analysis of the data revealed that spray with UAV sprayer is more efficient and precise in application and resulting in better control in late leaf spot foliar damage as the lowest percent disease incidence (PDI) was observed in T1 (24.58) followed by T2 (25.73) and then by T4 (25.88) which were on par with each other and PDI reduction percentages with respect to T5 are of 48.87, 44.65, 44.65 were observed in 2021-22, respectively. Similar results were found during 2022-23, i.e. the lowest PDI was observed in T1 (25.53) followed by T4 (27.75) and then T2 (28.33) which were on par with each other and reduction percentages of 51.20, 50.12, 48.51 were observed, respectively. The economic analysis through incremental cost-benefit ratio (ICBR) revealed that the highest ICBR ratio of 7.99 (T2) and 6.81 (T1) were realised and no phytotoxicity was observed in UAV spraying of fungicides in groundnut at low volume spraying of 25 L ha-1 without compromising the bio-efficacy